Intralayer magnetic ordering in Ge/Mn digital alloys - M. M. Otrokov and Arthur Ernst and Sergey Ostanin and G. Fischer and Pawel Buczek and Leonid M. Sandratskii and W. Hergert and Ingrid Mertig and V. M. Kuznetsov and E. V. Chulkov (Physical Review B, 2011)
We present a first-principles investigation of the electronic properties of Ge/Mn digital alloys obtained by the insertion of Mn monolayers in the Ge host. The main attention is devoted to the study of the magnetic properties of the Mn layers for various types of ordering of the Mn atoms. Depending on the type of Mn position three different structures are considered: substitutional, interstitial, and combined substitutional-interstitial. In all three cases numerical structural relaxation of the atomic positions has been performed. We find that the intralayer exchange parameters depend strongly on the crystal structure. For the substitutional and interstitial types of structure the stable magnetic order was found to be ferromagnetic. For the mixed substitutional-interstitial structure the ferromagnetic configuration appears unstable and a complex ferrimagnetic structure forms. The spin-wave excitations are calculated within the Heisenberg model. The critical temperatures of the magnetic phase transitions are determined using Monte Carlo simulations with interatomic exchange parameters obtained for two different magnetic reference states: a ferromagnetic and a disordered local moment state. © 2011 American Physical Society.